The Effect of Discovery Learning on The Development and Strengthening of Understanding Basic Concepts in Biology Based on Students’ Experiences - Susi Martini Sudibjo (Bioma : Jurnal Ilmiah Biologi, 2023)
The Indonesian government is currently implementing two types of curriculums, namely the 2013 curriculum and the ‘Merdeka belajar’ curriculum which has been implemented for 2 years. Both of these differently named curriculums run together at different academic grades throughout Indonesia. Although they have different names, both curriculums have similarities in the application of their learning process, which is inquiry-based learning. Teachers can apply inquiry-based learning based on the guidelines specified in the curriculum or implement other inquiry-based learning methods, one of which is Wenning's levels of inquiry. This study aims to develop and strengthens the understanding of basic concepts in biology based on the student experience. This study investigates the impact of discovery learning on the development and strengthening of understanding basic concepts in biology, based on the experiences of students. The research aimed to explore the effectiveness of a discovery learning approach in enhancing students' comprehension and retention of fundamental biological principles. This study emphasizes the value of discovery learning as a powerful pedagogical approach for facilitating students' comprehension and mastery of basic concepts in biology. After carrying out the learning process with discovery learning steps, students get reinforcement of the basic concepts of the food digestive system and make it easier for students to carry out the next stage of inquiry.